PARADOKS ADVOKASI PENDIDIKAN: ANTARA PRESTISE AKADEMIK DAN GIMIK PEMASARAN - Hadiq Syifa Al fawaz; Muhammad Sidiq Purnomo (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
The main objective of this study is to conduct an in-depth analysis and identify how SMK Puspa Bangsa 2 balances the pressure to maintain academic prestige with the need for appealing (often gimmicky) marketing strategies in its efforts to attract and retain prospective students, as well as to evaluate the impact of this balance on the school's image and perceived educational quality. This study uses a descriptive qualitative approach with a single case study strategy at SMK Puspa Bangsa 2 to understand the paradox between academic prestige and marketing strategies. Data were collected through in-depth interviews with the principal, marketing team, teachers, students, and parents; participatory observation of promotional activities; and document analysis, such as brochures and academic reports. Data analysis was conducted using thematic techniques. Validity was ensured through triangulation and member checking, and research ethics were upheld through written consent and the protection of informants' identities. This approach enables a deep understanding of the impact of marketing on the school's image and quality. The results of this study indicate that a crisis of trust at SMK Puspa Bangsa 2 arises due to an imbalance between symbolic marketing strategies and the actual quality of education. Excessive visual promotion is not matched by academic transparency, resulting in disappointment and a decline in student loyalty. The community's positive perception is more shaped by social media imagery than by actual quality. Therefore, the school needs to shift its communication strategy to be more honest and educational, and to empower the public to critically and rationally assess educational quality-not merely based on visual appearances..